The significant risk factors of intra-operative hemorrhage during laparoscopic myomectomy: A systematic review - Zaki Sleiman; Rania El Baba; Simone Garzon; Aline Khazaka (Wolters Kluwer Medknow Publications, 2020)
Laparoscopic myomectomy (LM) is becoming increasingly common in the management of uterine myomas and is usually offered regardless of the number, location, and size of the myomas. It has a generally low rate of periprocedural complications and is preferred to laparotomy for several reasons that are not limited to decreased length of hospital stay, number of sutures, smaller incisions, and decreased pain. However, blood loss during LM remains a challenge. To be able to stratify patients and provide better management after LM, it is crucial to identify these predictors of blood loss. Therefore, the aim of this review was to identify the risk factors for periprocedural blood loss after laparoscopic uterine myomectomy. According to our data synthesis, age, body mass index, and phase of the menstrual cycle do not seem to affect the blood loss during LM. Conversely, size and number of myomas, as well as operative time, was directly related to the increase of blood loss.